The Political Thinking and its Effect in The Development of the management Concept. - Zreka, Easera; Ibrahim, Ahmad (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
There is an important and basic relation ship between the political and ideological thin king and the management. What distinguishes the modern political thinking is its concern with the concept of management because of its importance in the life of peoples by developing all the economical, political, social, cultural and educational institutions for all the countries. The civilized communities which are developed economically, politically, socially and intellectually gives a great importance to the concept of management and they work to develop it to serve the society with all its various sides.